Therapy Expectations of Adolescents with Depression Entering Psychodynamic Psychotherapy: A Qualitative Study. (2nd January 2017) - Weitkamp, Katharina; Klein, Eva; Hofmann, Helmut; Wiegand-Grefe, Silke; Midgley, Nick
ABSTRACT: Patient expectations about therapy have been regarded as a common factor affecting the course and outcome of psychotherapy. However, little is known about the expectations of adolescents. We aimed to explore the therapy expectations of young people (YP) with depression prior to psychotherapy. We conducted semi-structured interviews with six YP (5 female, 15–19 years old) entering psychodynamic outpatient treatment. Interviews were transcribed verbatim and analyzed using Interpretative Phenomenological Analysis. The careful analysis of the YPs' accounts yielded the following four key themes: not knowing but being cautiously hopeful; therapy as a long and difficult process; therapy as a place to understand oneself and to develop ; and the importance of the professional and interpersonal skills of the therapist . The findings suggest to foster realistic treatment and outcome expectations while at the same time individual therapists should pay careful attention to the specific expectations that YP bring into therapy.